Peluang dan Tantangan Implementasi Pajak Karbon dalam Mendorong Ekonomi Hijau di Indonesia - Rahmawati, Zahra Aulia; Koerniawati, Dwi (Magister Ilmu Akuntansi Universitas Jambi, 2026)
Sustainable economic growth and carbon emission management have become key issues on the global agenda, prompting various countries, including Indonesia, to adopt economy-based emission control instruments. Carbon tax is a fiscal instrument that is considered effective for internalizing the external costs of emissions and encouraging the transition to a green economy. This study analyzes the opportunities and challenges of its implementation in Indonesia using a qualitative-descriptive method through a literature study of journals, regulations, and research reports. The results of the study show that conceptually and regulatively, Indonesia has a strong foundation through the 2021 HPP Lawand Presidential Regulation 98/2021. The opportunities for implementation include the potential for emission reductions of up to 30%, increased investment in renewable energy, the creation of green jobs, and projected state revenue of IDR 23.65 trillion. However, there are significant challenges such as industry resistance, the risk of inflation, suboptimal regulatory readiness, low public literacy, and the need for compensation mechanisms. The implementation of carbon taxes in Indonesia requires a mature roadmap, integration with ETS, and strengthened governance to support a sustainable green economy.